Aptamers as the Agent in Decontamination Assays (Apta-Decontamination Assays): From the Environment to the Potential Application In Vivo - Mawethu Pascoe, Bilibana; Citartan, Marimuthu; Tzi, Shien Yeoh; Timofey S., Rozhdestvensky; Tang, Thean Hock (Hindawi Publishing Corporation, 2017)
The binding specificity and affinity of aptamers have long been harnessed as the key elements in the development of aptamerbased assays, particularly aptasensing application. One promising avenue that is currently explored based on the specificity and affinity of aptamers is the application of aptamers in the decontamination assays. Aptamers have been successfully harnessed as the decontamination agents to remove contaminants from the environment and to decontaminate infectious elements. The reversible denaturation property inherent in aptamers enables the repeated usage of aptamers, which can immensely save the cost of decontamination. Analogous to the point-of-care diagnostics, there is no doubt that aptamers can also be deployed in the point-ofcare aptamer-based decontamination assay, whereby decontamination can be performed anywhere and anytime for instantaneous decision-making. It is also prophesied that aptamers can also serve more than as a decontaminant, probably as a tool to capture and kill hazardous elements, particularly pathogenic agents.